A super-toughened poly(lactic acid)-based thermoplastic vulcanizate through incorporating modified SiO2 nanoparticles. (28th July 2022) - Gong, Zhou; Huang, Jiarong; Fan, Jianfeng; Chen, Xiaoqing; Wang, Hui; Chen, Yukun
Abstract: Renewable and biodegradable poly(lactic acid) (PLA) has received great interest in the last decade. However, PLA exhibits high stiffness but low toughness, which largely restricts its applications. Blending with elastomers is a simple and effective method to improve the toughness of poly(lactic acid) (PLA), but the tensile strength of PLA generally decreases after adding elastomers. In this work, we manufacture the PLA/natural rubber (NR) (80/20) thermoplastic vulcanizate (TPV) with balanced stiffness-toughness through incorporating the modified SiO2 nanoparticles. The result of transmission electron microscopy, differential scanning calorimetry, and dynamic mechanical analysis shows that SiO2 nanoparticles modified by appropriate Bis-(3-triethoxysilylpropyl) tetrasulfide (TESPT) uniformly disperse in the interface, which not only enhances the strength of NR phase but also improves the interfacial compatibility of the PLA/NR TPV. Therefore, the toughness of the TPV could be improved (71.6 kJ/m 2 at room temperature and 7.61 kJ/m 2 at −30 °C) by adding low content of SiO2 nanoparticles (15 parts per hundreds of rubbers (phr) in NR or 3 phr in the TPV), while the tensile strength of the TPV remains at 34.6 MPa. Further, the co-continuous PLA/NR/SiO2 @TEPST TPVs have a potential to be applied in 3D printing field. Graphical abstract: Image 1